Transformasi Sosial: Peran Penting Kesetaraan Gender Dalam Pencapaian Hak Asasi Manusia - Zalfa Afifah Zahra; Ratu Shafiyyah Dara Zhafir; Cahya Ramdan Putra Mandayusdi; Hiratul Aprial; T Heru Nurgiansah (SMASH: Journal of Social Management Sains and Health, 2024)
Gender equality is a fundamental aspect of human rights, and this study aims to analyze it through a human rights lens. Utilizing normative juridical methods, the research examines existing literature, laws, and regulations pertaining to gender equality. The literature review reveals that women's rights are integral to human rights, with women often classified as vulnerable. International conventions and legislation are in place to uphold and safeguard women's rights and promote gender equality. Despite these efforts, achieving gender equality in Indonesia faces challenges. Cultural norms that prioritize women's domestic roles, limited awareness of women's rights, and societal stereotypes portraying women as weak contribute to these obstacles. Gender equality remains a pressing issue due to prevalent cases of gender-based injustice, including in Indonesia.